2007
DOI: 10.3844/ajassp.2007.491.495
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and Origin of Ultramfic Xenoliths from North Eastern Jordan Volcanoes

Abstract: The distribution of major, minor and trace elements in the Cenozoic alkali basalt from north-eastern Jordan indicates a homogeneous lava flow from a mantle source. These basaltic rocks contain abundant upper mantle xenoliths (spinal lherzolite, harzburgile and olivine- websterite). Theses xenoliths contain olivine, orthopyroxne, clinoporoxene and a few amounts of spinal. Their mineral assemblages, chemistry, texture and major elements abundances indicate they were derived and equilibrated under upper mantle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…The low content of SiO 2 (40.83 -47.55 ppm) and high content of MgO (6.3 -11.7 wt%) and total FeO (7.36 -15.42 wt%) indicated the natural fractionation of the MB. Furthermore, the high concentration of Cr (115 -324 ppm) is consistent with the earlier findings reported for primary magma (e.g., 257.6 ppm [5], 313.6 ppm [14], 241 ppm [31], and 125.3 ppm [43]). The high Mg≠ (average of 0.52) observed for MB in the present study is similar to that reported earlier for rocks affected by fractionation or accumulation of plagioclase, clinopyroxene, orthopyroxene, and olivine [35].…”
Section: Discussionsupporting
confidence: 80%
“…The low content of SiO 2 (40.83 -47.55 ppm) and high content of MgO (6.3 -11.7 wt%) and total FeO (7.36 -15.42 wt%) indicated the natural fractionation of the MB. Furthermore, the high concentration of Cr (115 -324 ppm) is consistent with the earlier findings reported for primary magma (e.g., 257.6 ppm [5], 313.6 ppm [14], 241 ppm [31], and 125.3 ppm [43]). The high Mg≠ (average of 0.52) observed for MB in the present study is similar to that reported earlier for rocks affected by fractionation or accumulation of plagioclase, clinopyroxene, orthopyroxene, and olivine [35].…”
Section: Discussionsupporting
confidence: 80%
“…The high concentration of Cr (18 to 385 ppm) with average 246.87 ppm is consistent with findings reported for primary magma |(e.g., 241 ppm [30], 257.6 ppm [11], 313.6 ppm [19], 125.3 ppm [46], 95 ppm [42]. The high Mg# (average 55.66) for RB is similar to that reported for rock affected by fractionation or accumulation of clinopyroxene, orthopyroxene, and olivine and plagioclase [34].…”
Section: Discussionsupporting
confidence: 68%
“…The ternary diagrams for Ti-Zr-Sr and Ti-Zr-Y diagrams (Figure 7(b) and Figure 7(c)) after [32], shows all the JDB Rock samples plotted within the calcalkaline basalt field. The MgO-FeO(tot)-Al 2 O 3 diagram after [38], shows the JDB rock samples were plotted within continental basaltic field (Figure 7(d) [39]. The high Mg# (average 46) for JDB is similar to that reported for rock affected by fractionation or accumulation of clinopyroxene, orthopyroxene, as well as olivine and plagioclase [40].…”
Section: Petrogensissupporting
confidence: 61%